A concepção de educação na Revista Vozes durante os debates da LDB (1956 a 1965): o período de Frei Aurélio Stulzer - Assis, Paula Maria de (2008)
The main goal of this research is to analyze the conception of education in Vozes de Petrópolis Magazine during the editorial management of Frei Alberto Stulzer, which is also the time of the discussion and implementation of Law Guidelines and Bases which were signed in 1961. As a matter of fact, this research has as the main source articles from the magazine itself, which is not only the source but also the main subject. As the object, it leads us to the Cultural History field. The magazine does not represent a society, in a specific moment, more than that, it represents the labor of a determined social configuration of imposing its image to the future. The hypothesis, that the Magazine worked as a vehicle for efficient communication, making the dialogue easier between various spheres that made up their public reader, is the basis of this project. The analysis, under this view, will allow us to identify the various areas of expertise of staff who wrote the articles in the Journal, and interpret the design of education they have demonstrated